Thermal stability of aluminum, molybdenum, tungsten, and chromium nanopowders and their mixtures; Russian Journal of Physical Chemistry A; Vol. 84, № 3 - Ilyin A. P. Aleksandr Petrovich (2010, 2010)
Our experimental studies have revealed that after the mixing of nanopowders and coarsely dispersed powders, the temperature of the start of oxidation of the mixture was not determined by the corresponding temperature of the thermally less stable component, but took a new constant value. This tendency was explained by the mutual effects of the binary electrical layers formed by redox reactions in the surface and subsurface layers of the particles of the powders being mixe.